2015
DOI: 10.1093/brain/awv241
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype characteristics and baseline natural history of heritable neuropathies caused by mutations in theMPZgene

Abstract: We aimed to characterize genotype-phenotype correlations and establish baseline clinical data for peripheral neuropathies caused by mutations in the myelin protein zero (MPZ) gene. MPZ mutations are the second leading cause of Charcot-Marie-Tooth disease type 1. Recent research makes clinical trials for patients with MPZ mutations a realistic possibility. However, the clinical severity varies with different mutations and natural history data on progression is sparse. We present cross-sectional data to begin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
101
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 119 publications
18
101
2
9
Order By: Relevance
“…However, our proband for the Thr65Asp mutation was a 13‐year‐old girl who could not walk independently until 19 months of age, was unable to run after 5 years of age and had median motor nerve conduction velocities of 6 meters/sec. Alternatively, the proband for the Arg227Ser mutation was a 44‐year‐old man who walked by a year, was a fast runner as a child playing on his varsity football team in high school, who did not develop symptoms until 40 years of age and had median MNCV of 32 met/sec 1. We also identified no correlation between UPR activation and disease severity, as measured by the CMTNS (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…However, our proband for the Thr65Asp mutation was a 13‐year‐old girl who could not walk independently until 19 months of age, was unable to run after 5 years of age and had median motor nerve conduction velocities of 6 meters/sec. Alternatively, the proband for the Arg227Ser mutation was a 44‐year‐old man who walked by a year, was a fast runner as a child playing on his varsity football team in high school, who did not develop symptoms until 40 years of age and had median MNCV of 32 met/sec 1. We also identified no correlation between UPR activation and disease severity, as measured by the CMTNS (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Clinical investigators in the INC had evaluated and reported on these patients and their respective symptoms, signs and physiology 1. We report our findings in the present manuscript.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations